Chapter 10. Psychiatric Conditions (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
AuthorMiss Aliya Rayyesa MirzaaPharmD Scholar, Department of Pharmacy Practice, Joginpally B.R. Pharmacy College, Telangana, IndiaAbstractPharmacological interventions in psychiatric disorders require systematic assessment of symptom profiles, severity metrics, and functional impairment indicators. Depression management incorporates selective serotonin reuptake inhibitors, novel antidepressants, and augmentation strategies, with emphasis on response monitoring and suicide risk assessment. Anxiety disorder treatment utilizes multiple medication classes including antidepressants, anxiolytics, and psychological interventions based on specific disorder characteristics. Bipolar disorder management requires careful selection of mood stabilizers, antipsychotics, and maintenance strategies with monitoring of mood cycles and metabolic parameters. Schizophrenia treatment incorporates first and second-generation antipsychotics with selection based on efficacy profiles, side effect burden, and adherence factors. Sleep disorder protocols utilize targeted interventions for specific sleep pathologies while considering safety profiles and dependency risks. Treatment strategies emphasize long-term outcome optimization through systematic monitoring of therapeutic response, adverse effects, and functional recovery.Keywords: Psychopharmacology, Mood disorders, Antipsychotic therapy, Anxiety treatment, Sleep managementVIEW PDF